Kewajiban Filial dan Ketidakadilan Warisan terhadap Anak Perempuan Perawat - Habib Ismail; Didik Kusno Aji Nugroho; Mufid Arrasyid; Muhammad Anjas (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the relationship between filial obligation and inheritance inequality experienced by daughters as caregiving daughters in Muslim families from a gender perspective. It aims to analyze the social construction of filial obligations, the recognition of caregiving contributions, and the reproduction of gender inequality in inheritance practices. The study employs an empirical legal approach using qualitative methods in Central Lampung Regency, East Lampung Regency, and Metro City, Indonesia. Data were collected through in-depth interviews, observation, and document analysis and were analyzed using Filial Obligation Theory, Patriarchy Theory, Distributive Justice Theory, and the concept of living law. The findings indicate that filial obligations have become feminized through patriarchal norms that position daughters as the primary caregivers for aging parents. Although they devote substantial time, effort, health, and economic resources to caregiving, care work is generally regarded as a moral obligation rather than an economic contribution relevant to inheritance distribution. This practice reveals a gap between formal justice based on heirship status and substantive justice based on actual contributions to family welfare. This study introduces the concept of Caregiving-Based Inheritance Inequality, referring to inheritance injustice arising from the failure to recognize caregiving contributions. The findings advocate for the development of more gender-responsive inheritance law by integrating the value of care work as a consideration of substantive justice within the family.